2018
DOI: 10.3390/epigenomes3010001
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Regulation of EMT (Epithelial to Mesenchymal Transition) and Tumor Aggressiveness: A View on Paradoxical Roles of KDM6B and EZH2

Abstract: EMT (epithelial to mesenchymal transition) is a plastic phenomenon involved in metastasis formation. Its plasticity is conferred in a great part by its epigenetic regulation. It has been reported that the trimethylation of lysine 27 histone H3 (H3K27me3) was a master regulator of EMT through two antagonist enzymes that regulate this mark, the methyltransferase EZH2 (enhancer of zeste homolog 2) and the lysine demethylase KDM6B (lysine femethylase 6B). Here we report that EZH2 and KDM6B are overexpressed in num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 99 publications
(134 reference statements)
0
7
0
Order By: Relevance
“…Tumor metastasis and cell migration modulated by the epithelial mesenchymal transition (EMT) pathway are important in the development of various cancers 38 . Since many aggressive tumors were reported to overexpress EZH2, it was suggested that this protein act as an important regulator of the development of EMT 39 . Consistent with the previous prediction with web-based bioinformatics, we examined the mRNA level of the EMT genes in EZH2-treated YM-1 and KYSE-30 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Tumor metastasis and cell migration modulated by the epithelial mesenchymal transition (EMT) pathway are important in the development of various cancers 38 . Since many aggressive tumors were reported to overexpress EZH2, it was suggested that this protein act as an important regulator of the development of EMT 39 . Consistent with the previous prediction with web-based bioinformatics, we examined the mRNA level of the EMT genes in EZH2-treated YM-1 and KYSE-30 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Like EMT, epigenetic modifications-such as DNA or histone methylation, and histone acetylation-are also reversible, and have been shown to play a pivotal role in EMT regulation, which makes them attractive targets for novel chemotherapeutics (12). Interactions between key EMT transcription factors and enzymes that modify DNA/histones have been reviewed in detail (3,10,13,14).…”
Section: Introductionmentioning
confidence: 99%
“…Both EZH2 and KDM6B, two proteins with opposite catalytic activities, have previously been associated with cancer aggressiveness or EMT. Indeed, a high expression of EZH2 was associated with metastasis and a poor clinical outcome in clear cell renal cell carcinoma, esophagus squamous cell carcinoma, bladder urothelial carcinoma, cutaneous melanoma, hormone-refractory and metastatic prostate cancer, gastric carcinoma, breast carcinoma, lung carcinoma and ovarian carcinoma, as well as in pediatric brain tumors (for a review, see Lachat et al [21]). However, KDM6B expression has also been correlated with metastasis in clear cell renal cell carcinoma, ovarian cancer, myeloma, hepatocellular carcinoma, malignant pleural mesothelioma, and Hodgkin's lymphoma or invasive breast tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, KDM6B, although far less studied, has been positively associated with EMT or metastasis in renal cancer or hepatocarcinoma [19,20]. Although these paradoxical roles have been recently discussed [21], it remains unclear how these proteins, with apparent opposite activities, could both promote EMT and/or cancer aggressiveness. To address this question, and in order to better understand the respective roles of EZH2 and KDM6B during EMT, we decided, for the first time, to simultaneously study these proteins in in vivo and in vitro models.…”
Section: Introductionmentioning
confidence: 99%